2018
DOI: 10.1248/bpb.b18-00283
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Euphorbiaceae Plant Extracts for Anti-5α-reductase

Abstract: In our research program to find novel agents for alopecia from natural plant resources, we screened Euphorbiaceae plant extracts using an anti-5α-reductase assay. Among the samples tested, the extract of Phyllanthus urinaria showed the most potent activity with 24.3 and 64.6% inhibition at 50 and 200 µg/mL against the enzyme, respectively. The extract also suppressed the androgen activity of dihydrotestosterone in LNCaP cell line. These results show that the extract of P. urinaria may be a multi-potent agent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Another PS, stigmasterol, was reported to be associated with a reduction in common cancer risks including colon cancer, breast cancer and CaP ( Bradford & Awad, 2007 ). Kamei et al (2018) studied Phyllanthus urinaria where the extract was shown to suppress androgen activity of DHT in LNCaP cell lines and has inhibitory activity against 5αRs, of which the active bioactive compound responsible for the activity was identified as stigmasterol isolated from an activity-guided fractionation. An in vitro study of Serenoa repens extract (SPE) using baculovirus-directed insect cell expression system demonstrated the inhibition of both 5αR1 and 5αR2 in a non-competitive and uncompetitive manner, respectively ( Iehlé et al , 1995 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another PS, stigmasterol, was reported to be associated with a reduction in common cancer risks including colon cancer, breast cancer and CaP ( Bradford & Awad, 2007 ). Kamei et al (2018) studied Phyllanthus urinaria where the extract was shown to suppress androgen activity of DHT in LNCaP cell lines and has inhibitory activity against 5αRs, of which the active bioactive compound responsible for the activity was identified as stigmasterol isolated from an activity-guided fractionation. An in vitro study of Serenoa repens extract (SPE) using baculovirus-directed insect cell expression system demonstrated the inhibition of both 5αR1 and 5αR2 in a non-competitive and uncompetitive manner, respectively ( Iehlé et al , 1995 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to an in vitro study performed by Marisa Cabesa and her colleagues on hamster prostate tissue, SIT inhibits 5-αR in a dose-dependent manner (IC 50 = 1.1 µg/mL compared to finasteride with IC 50 = 0.003 µg/mL) [59]. Other data have shown that stigmasterol, extracted from Phyllanthus urinaria, also inhibits 5-αR and is less potent than SIT (IC 50 = 11.2 µg/mL) [60]. To offset the low efficacy of PSs, a combination of conventional treatments with PSs may provide some clinical benefit.…”
mentioning
confidence: 99%